The strange reincarnations of Hendrik Verloom - Clifford, Eth, 1915- (Boston : Houghton Mifflin, 1982)
Anna, already worried by her grandfather's insistence that he has led many previous lives, begins to fear that he is responsible for a series of hoaxes plaguing their apartment building.
Keywords: Grandfathers -- Fiction; Reincarnation -- Fiction; Impersonation -- Fiction; Apartment houses -- Fiction